Study of prevalence of theileriosis in cattle and evaluation of therapeutic efficacy of different commercially available drugs (Asian Journal of Medical and Biological Research, 2022)
The present study was carried out to detect the prevalence of theileriosis in cattle of Sadar, Singair and Ghior upazila in Manikganj district of Bangladesh and evaluate the therapeutic efficacy of Imidocarb dipropionate (Babenil®), Oxytetracycline (Renamycine®) and Gentamicin (Acigent®). The study was conducted for six months and during this study period a total of 150 cattle were examined, 10 were found to be infected with Theileria spp. On Geimsa stained blood smear examination, it was observed that the overall prevalence of theileriosis in cattle was recorded as 6.67%. Animals were screened on the basis of clinical signs like fever, anorexia, with or without superficial lymph node enlargement and blood smear examination for presence of Theileria spp. The prevalence of theileriosis in female was non significantly higher (7.50 %) than male (5.71%). In case of age group, the significantly highest prevalence (13.3%) was in adult cattle above 3 years age, followed by 4.00 % in the age group of 2 to less than 3 years old and 0.00 % in 6 months to 2 years which was not significant(p>0.05). The prevalence of theileriosis in respect of breed was non significantly (p>0.05) maximum in cross breed cattle (7.05 %) than in indigenous cattle (6.15%). After identification of causal agent, therapeutic effect of imidocarb dipropionate, oxytetracycline and gentamicin were tested and where highest recovery was found by administration of imidocarb dipropionate (70 %) can be successfully used in the treatment of theileriosis.Asian J. Med. Biol. Res. 2022, 8 (1), 1-8